2005
DOI: 10.1016/j.jasms.2005.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Direct correlation of the crystal structure of proteins with the maximum positive and negative charge states of gaseous protein ions produced by electrospray ionization

Abstract: Electrospray mass spectrometric studies in native folded forms of several proteins in aqueous solution have been performed in the positive and negative ion modes. The mass spectra of the proteins show peaks corresponding to multiple charge states of the gaseous protein ions. The results have been analyzed using the known crystal structures of these proteins. Crystal structure analysis shows that among the surface exposed residues some are involved in hydrogen-bonding or salt-bridge interactions while some are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 60 publications
2
54
0
Order By: Relevance
“…Next, we propose a simple mathematical model based on the results of these atomistic investigations. This model has no adjustable parameters and it reproduces the well-known correlations between the protein net charge, q, and both mass [10] and solvent-exposed surface [17]. Our model hints to GB app as a key factor for the ionization of folded proteins, suggesting that protein ionization depends on intrinsic properties of the protein structure and on the GB of the solvent [4].…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Next, we propose a simple mathematical model based on the results of these atomistic investigations. This model has no adjustable parameters and it reproduces the well-known correlations between the protein net charge, q, and both mass [10] and solvent-exposed surface [17]. Our model hints to GB app as a key factor for the ionization of folded proteins, suggesting that protein ionization depends on intrinsic properties of the protein structure and on the GB of the solvent [4].…”
Section: Introductionmentioning
confidence: 63%
“…However, it might not necessarily hold for side chains. To [17] tackle this issue, the present study employs a combined MC/ MD sampling scheme using the OPLS/AA force field with GB corrections. Indeed, standard force fields for biomolecular simulations are unable to describe bond breaking and forming.…”
Section: Protomer Space Explorationmentioning
confidence: 99%
“…The two charge-state distributions may represent the following: conformation 1: A disordered state that when electrosprayed, yields more charging due to exposure of amino acid side chains, and less cation binding due to disordered binding structures. Indeed, Prakash and Mazumdar [81] showed that the higher charged states in positive ion ESI-MS are a consequence of unfolding, affording a greater number of surface basic groups. Denatured calmodulin also sprays with higher charge states than does the wild type [82].…”
Section: Spectroscopymentioning
confidence: 99%
“…Nevertheless, X-ray or NMR structures were not used to determine the exact number of salt bridges and their localization on the surface of the protein. This effort was later on made by Prakash and Mazumdar [40]. They showed that salt bridges and hydrogen bonds must be taken into account to determine the maximum charge state of protein in the positive and negative ion modes.…”
Section: Resultsmentioning
confidence: 99%